Biking around the Metro a visualization of anthropocene - Varron, Salvador Luis L.; Abaño, Ma. Victoria; Romero, Riza (Quezon City College of Fine Arts, University of the Philippines Diliman, 2017)
As an artist, it's our role to create artworks that criticize the situation in our current period. The concept of this thesis was formed through my experiences in biking around the Metro. As a cyclist, it is a requirement to be aware of the surroundings and the environment I am in. Part of what I have observed in my travels is the atmosphere, especially the clouds and how they are always under a constant process of change just like everything else around me. My experience in biking through an urban landscape exposed me to learn that this landscape itself is built through synthetics. In this thesis, I utilized the image of clouds as a metaphor for the concept of change. The question formed is regarding where these changes will lead to: an ecological balance or a synthetic lifestyle. Plastic was the material chosen because of its accessibility as a global product and how it is a product brought about by overproduction in connection with capitalism and modernity. This project was built as an attempt to extend my experience to an audience and to trigger retrospection regarding the state of the environment. Through this, my perspective and views regarding biking in connection with being environmentally aware was developed. In doing all of this, I have turned a personal experience into a collective one.
Thesis (Bachelor of Fine Arts (Painting))--University of the Philippines Diliman
Keywords: Visualization; Anthropocene